Bis‐molybdopterin guanine dinucleotide modulates hemolysin expression under anaerobiosis and contributes to fitness in vivo in uropathogenic Escherichia coli. Issue 4 (20th September 2021) - Zhang, Xinyang; Huang, Dongyan; Zhao, Zihui; Cai, Xuwang; Cai, Wentong; Li, Ganwu
Abstract: Uropathogenic Escherichia coli (UPEC) is the primary causative agent of urinary tract infections (UTIs). Successful urinary tract colonization requires appropriate expression of virulence factors in response to host environmental cues, such as limited oxygen and iron availability. Hemolysin is a pore‐forming toxin, and its expression correlates with the severity of UPEC infection. Previously, we showed that hemolysin expression is enhanced under anaerobic conditions; however, the genetic basis and regulatory mechanisms involved remain undefined. Here, a transposon‐based forward screen identified bis ‐molybdopterin guanine dinucleotide cofactor ( bis ‐MGD) biosynthesis as an important factor for a full transcription of hemolysin under anaerobiosis but not under aerobiosis. bis ‐MGD positively influences hemolysin transcription via c3566‐c3568, an operon immediately upstream of and cotranscribed with hlyCABD . Furthermore, suppressor mutation analysis identified the nitrogen regulator NtrC as a direct repressor of c3566‐c3568 ‐ hlyCABD expression, and intact bis ‐MGD biosynthesis downregulated ntrC expression, thus at least partially explaining the positive role of bis ‐MGD in modulating hemolysin expression. Finally, bis ‐MGD is involved in hemolysin‐mediated uroepithelial cell death and contributes to the competitive fitness of UPEC in a murine model of UTI. Collectively, our data establish that bis ‐MGD biosynthesis plays a crucial role in UPEC fitness in vivo, thus providing a potential target for combatting UTIs. Abstract : Pore‐forming hemolysin is an important virulence factor in uropathogenic Escherichia coli (UPEC), which correlates with the disease severity. Transposon screening identified bis ‐molybdopterin guanine dinucleotide cofactor ( bis ‐MGD) biosynthesis as an important factor for full transcription of hemolysin under anaerobiosis in UPEC. Mechanistically, intact bis ‐MGD biosynthesis keeps ntrC transcription in check, and NtrC serves as a direct repressor of hemolysin expression.